Peningkatan SDM Pendidikan Keagamaan Melalui Kaderisasi Ustadz dan Ustadzah Masyarakat di Dusun Langgeng Desa Karangluhur - Ibnu Alif Utomo; Dian Asmarajati (Jurnal Pengabdian Masyarakat PGSD, 2022)
The low level of human resources affects in terms of education and religion practice. One of the examples is the lack of ustadz who can teach reading and writing the Qur'an. The purpose of this activity is how to regenerate new prospective ustadz and ustadzah to assist in reading and writing the Qur'an in Langgeng Hamlet, Karangluhur Village, Kertek District, Wonosobo Regency. The community service method uses observation, interviews, and documentation. The stages are through a preliminary interview, direct observation, teaching practice, direction, support and supervision of prospective clerics and clerics in carrying out the practice of reading and writing the Qur'an at TPQ. The results of integrated service include: First, training and also learning that is followed by prospective ustadz and ustadzah can provide knowledge and also learn how to teach reading and writing the Qur'an. Second, mentoring and motivation are carried out so that prospective ustadz and ustadzah have enthusiasm and confidence in teaching reading and writing the Qur'an. Third, with this community service activity, initially there were only 2 ustadz in carrying out reading and writing activities of the Qur'an to be helped by the presence of new ustadz and ustadzah candidates. Fourth, the implementation of activities still has obstacles in the lack of motivation and awareness of the parents, but can be overcome with regular supervision. This activity was responded positively by the community, especially those that focus on religious education and can also be used as an alternative example of strengthening potential for villages or other areas with similar conditions